Uniwersytet w krajobrazie kulturowym wojewodztwa lubuskiego na podstawie danych GUS za lata 2013-2023 = The university in the cultural landscape of the Lubuskie Voivodeship based on data from the central statistical office (GUS) for the years 2013-2023 - Grzegorczyk, Milena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to present the position of the university in the cultural space of the Lubuskie Voivodeship. The analysis is based on statistical data from the Central Statistical Office (GUS), including, among others, the number of students and graduates in the region, as well as participation in cultural activities and the operation of cultural institutions.
Keywords: kapitał kulturowy; województwo lubuskie; uniwersytet; dane statystyczne; analiza danych zastanych; cultural capital; lubuskie voivodeship; university; statistical data; secondary data analysis